Determinants of dividend policy on blue-chip stock of companies listed in Bursa Malaysia / Muhammad Nurhishamuddin Amiruddin - Amiruddin, Muhammad Nurhishamuddin (Faculty of Business Management, 2017)
This research aims to investigate the determinants of dividend policy on blue-chip stock of companies listed on Bursa Malaysia over for five years from 2011 to 2015. Twenty six companies had been selected that listed as blue-chip stock and total observation is 130. This study employs multiple regression analysis to measure relationship variable and overall impact on dividend policy and to test the operational hypotheses. A secondary data was used as the main instrument in gathering data. The study also investigates the relationship between dividend policy with earning per share, price earning, long term debt and debt ratio. This model was tested using Eviews software application and test use related with the data. The finding of this research shows that there has related and interrelated among dividend policy with earning per share, price earning, long term debt and debt ratio.